Effect of unplanned spontaneous follicular growth and ovulation on pregnancy outcomes in planned artificial frozen embryo transfer cycles: a propensity score matching study. Issue 6 (25th March 2021) - Su, Yan; Ji, Hui; Jiang, Wei; Xu, Lu; Lu, Jing; Zhao, Chun; Zhang, Mianqiu; Cao, Shanren; Ling, Xiufeng; Shen, Rong
Abstract: STUDY QUESTION: Does unplanned spontaneous follicular growth and ovulation affect clinical outcomes after planned artificial frozen-thawed embryo transfer (AC-FET) cycles? SUMMARY ANSWER: AC-FET and spontaneous follicular growth and ovulation events resulted in notably better pregnancy outcomes with a significantly higher implantation rate (IR), clinical pregnancy rate (CPR), ongoing pregnancy rate (OPR) and live birth rate (LBR) and a significantly lower miscarriage rate. WHAT IS KNOWN ALREADY: The AC-FET protocol without GnRH agonist administration is associated with a low incidence of follicular growth and ovulation. In the literature, authors often refer to these types of cycles with concern due to possibly impaired FET outcomes. However, the real impact of such cycles has yet to be elucidated due to the lack of existing data. STUDY DESIGN, SIZE, DURATION: This was a retrospective clinical study involving 2256 AC-FET cycles conducted between January 2017 and August 2019. Propensity score (PS) matching was used to control for confounding variables. PARTICIPANTS/MATERIALS, SETTING, METHODS: Subjects were divided into two groups: a study group: cycles with spontaneous follicular growth and ovulation (the maximum diameter of follicles in any ovary was ≥14 mm and ovulation was confirmed by consecutive ultrasound examinations) and a control group featuring cycles without growing follicles (the maximum diameter of follicles in both ovaries were <10 mm). The study group was matched by PS with the control group at a ratio of 1:2. The study group consisted of 195 patients before PS matching and 176 patients after matching. The numbers of participants in the control group before and after PS matching were 2061 and 329, respectively. MAIN RESULTS AND THE ROLE OF CHANCE: This analysis showed that patient age (adjusted odds ratio [aOR] 1.05; 95% CI 1.01–1.09; P= 0.010) and basal FSH level (aOR 1.06; 95% CI 1.01–1.11; P= 0.012) were significantly and positively related with the spontaneous follicular growth and ovulation event. In addition, this event was negatively correlated with BMI (aOR 0.92; 95% CI 0.87–0.97; P= 0.002), AMH level (aOR 0.66; 95% CI 0.59–0.74; P< 0.001) and a high starting oestrogen dose (aOR 0.53; 95% CI 0.38–0.76 for 6 mg vs. 4 mg; P< 0.001). Baseline characteristics were similar between groups after PS matching. Patients in the study group had a significantly higher IR (28.8% vs. 21.8%, P= 0.016), CPR (44.9% vs. 33.4%, P= 0.011), OPR (39.2% vs. 26.1%, P= 0.002) and LBR (39.2% vs. 24.9%, P= 0.001) and a lower miscarriage rate (12.7% vs. 25.5%, P= 0.030), compared with those in the control group. LIMITATIONS, REASONS FOR CAUTION: This was a retrospective study carried out in a single centre and was therefore susceptible to bias. In addition, we only analysed patients with normal ovulation patterns and excluded those with follicular growth but without ovulation. Further studies remain necessary to confirm our results. WIDER IMPLICATIONS OF THE FINDINGS: It is not necessary to cancel cycles that experience spontaneous follicular growth and ovulation. Our data support promising clinical outcomes after this event. Our findings are important as they can better inform clinicians and patients. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by National Natural Science Foundation of China (grant no. 81701507, 81801404, 81871210, 82071648), Natural Science Foundation of Jiangsu Province (grant no. BK20171126, BK20201123) and Jiangsu Province '333' project. The authors declare that they have no competing interests. TRIAL REGISTRATION NUMBER: N/A.